2014
DOI: 10.1111/papr.12194
|View full text |Cite
|
Sign up to set email alerts
|

Spinal Cord Stimulation of the Dorsal Root Ganglion for Groin Pain—A Retrospective Review

Abstract: Early findings suggest that neuromodulation of the DRG may be an effective treatment for chronic neuropathic pain conditions in the groin region. This technique offers a useful alternative for pain conditions that do not always respond optimally to traditional SCS therapy. Neuromodulation of the DRG provided excellent cross-dermatomal paresthesia coverage, even in cases with patients with discrete pain areas. The therapy can be specific, sustained, and independent of body position.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
103
0
2

Year Published

2015
2015
2021
2021

Publication Types

Select...
5
5

Relationship

2
8

Authors

Journals

citations
Cited by 111 publications
(107 citation statements)
references
References 25 publications
(38 reference statements)
2
103
0
2
Order By: Relevance
“…Further surgical treatment can be achieved by anterior or posterior selective or triple neurectomy with [16]. Other treatment options include paravertebral nerve blockage or spinal cord stimulation of the dorsal root ganglion [17]. However, it is important to mention that surgical intervention holds risks such as chronic ongoing pain, hypersensitivity, permanent numbness, denervation of the oblique muscles, testicular atrophy, and neuroma formation [11].…”
Section: Discussionmentioning
confidence: 99%
“…Further surgical treatment can be achieved by anterior or posterior selective or triple neurectomy with [16]. Other treatment options include paravertebral nerve blockage or spinal cord stimulation of the dorsal root ganglion [17]. However, it is important to mention that surgical intervention holds risks such as chronic ongoing pain, hypersensitivity, permanent numbness, denervation of the oblique muscles, testicular atrophy, and neuroma formation [11].…”
Section: Discussionmentioning
confidence: 99%
“…Importantly, paresthesia coverage can remain stable through 12 months . In follow‐up postmarket studies, stability of paresthesia and pain relief has been demonstrated over 15 months . Combined with the lack of positional effects (that is, differences in paresthesia intensity when standing vs. lying down) , DRG‐SCS may provide some solutions for common complaints with SCS therapy.…”
Section: Discussionmentioning
confidence: 99%
“…There is also positive ability in the target region to induce stimulation coverage for those areas, which SCS would not be able to reach, for example, toes and foot [15, 16]. Additionally, the stimulation parameters require a lower demand in energy consumption.…”
Section: Discussionmentioning
confidence: 99%